Коммуникaтивные особенности интонaции в современном корейском языке (Вестник КазНУ. Серия Востоковедения, 2017)
This article examines the problems of speech which system of Russianlanguage in comparison to the sound system of Korean language. Speechthat reported in optical marks will not be perceived by human, it willremain as a dead sign. It becomes an authentic speech only when thereis an act of communication, when it is read or at least when it is soundedsilently in mind. Sounding speech transfers the information better thanthe written characters. Two things are the most important in cross-culturalcommunication, they are the perception of speech, that is the reading (orlistening to) in one language, and the end of the action, that is speaking (orwriting) in another language. The perception in one language and expressingin another is one of the difficulties in communication. To overcome thedifficulties and achieve the correct pronunciation can be achieved by asystem of exercises for the development of phonemic hearing.